A solid-state battery capable of 180 C superfast charging and 100% energy retention at –30 °C - Hu Hong; Zhiquan Wei; Yiqiao Wang; Xinru Yang; Xun Guo; Qingshun Nian; Xinliang Li; Qing Li; Shixun Wang; Shimei Li; Dechao Zhang; Qi Xiong; et al. (Proceedings of the National Academy of Sciences, 2025)
Solid-state electrolytes (SSEs) are being extensively researched as replacements for liquid electrolytes in future batteries. Despite significant advancements, there are still challenges in using SSEs, particularly in extreme conditions. This study presents a hydrated metal-organic ionic cocrystal (HMIC) solid-state ion conductor with a solvent-assisted ion transport mechanism suitable for extreme operating conditions. Through crystal engineering strategies, the adsorption capacity of HMIC for anions and water molecules can be regulated, thereby facilitating cation hopping transport and enhancing electrochemical stability. As a result, optimized HMIC shows exceptional properties, including an extraordinarily high Zn 2+ transference number (t Zn2+ = 0.81), an expanded electrochemical stability window (~2.6 V), and an exceptionally high Zn 2+ ion conductivity (8.6 mS cm –1 , 25 °C). Interface dynamics analysis indicates that this strong binding to water molecules can significantly reduce the desolvation energy barrier and enhance the ionic diffusion coefficient. (10 to 100 times higher than that in aqueous electrolytes). This allows Zn|| Prussian blue analog batteries to exhibit impressive fast-charging performance (180 C, 20 s, over 1,000 charge/discharge cycles) and maintain 100% discharge capacity retention and discharge plateau from –30 to 30 °C. The development of HMICs with a solvent-assisted hopping mechanism provides a promising path for solid-state zinc-ion batteries in extreme conditions, including fast charging, low temperature, and high loading.